TUBUH DALAM KOMEDI - ldfie Widya Pratama (IKOM UMY, 2015)
Funny scenes that use body as a medium for producing humor is very often encountered in a variety of shows on television, especially on programs comedy talk show genre. Then, how humor wos creoted can be viewed from various perspectives, among other expressions of the form of funny, until the production process that humor. The results showed that body-themed humor that appeors in the talk show Bukon Empat lvlatalJntung Ado Budi, is more likely to leod to an unattractive body shape (notaccording to,standard,) as a commodity. Theme of humor body that can producelaughter does not only come from the techniques (visually) in producing thot humor, butalso involves the relotions with the surrounding environment, because in each of humors that is created there is olways a connection between: a funny scene, funny understanding, and the place where the humor is produced